The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1080/0028825x.1989.10414119
|View full text |Cite
|
Sign up to set email alerts
|

Forest succession on landslides in the Fiord Ecological Region, southwestern New Zealand

Abstract: Primary succession to montanerain forest on the bare slip faces of landslides is described from three variously aged slides with plot and plotless data, 24 years after a previous study, and is related to adjacent mature forest. Over a 15-102 yr period striking successional changes occurred in both vegetation and flora.The dominant pioneer, Leptospermum scoparium, persists with decreasing importance in the canopy beyond a century, with regeneration falling completely from the seventh decade. Although some speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 37 publications
(37 reference statements)
2
27
0
Order By: Relevance
“…He also found higher light levels, more extreme temperatures, greater moisture stress due to enhanced evapotranspiration, and continuing substrate instability on the steep upper slopes of landslide scars. Numerous recent studies have similarly reported lower nutrient levels (Reddy and Singh, 1993;Dalling and Tanner, 1995), more extreme temperatures (Mark et al, 1989), and continuing substrate instability (Hunter and Parker, 1993) on landslides relative to terrain adjacent to landslide scars. Many have reported a predominance of pioneer species on landslide scars (e.g., Miles and Swanson, 1986;Guariguata, 1990;Simon et al, 1990;Mark et al, 1989); on sites characterized by repeated failure, pioneers may dominate indefinitely (Orme, 1990;cf.…”
Section: Slopes Affected By Slope Failure and Mass Movementmentioning
confidence: 85%
See 2 more Smart Citations
“…He also found higher light levels, more extreme temperatures, greater moisture stress due to enhanced evapotranspiration, and continuing substrate instability on the steep upper slopes of landslide scars. Numerous recent studies have similarly reported lower nutrient levels (Reddy and Singh, 1993;Dalling and Tanner, 1995), more extreme temperatures (Mark et al, 1989), and continuing substrate instability (Hunter and Parker, 1993) on landslides relative to terrain adjacent to landslide scars. Many have reported a predominance of pioneer species on landslide scars (e.g., Miles and Swanson, 1986;Guariguata, 1990;Simon et al, 1990;Mark et al, 1989); on sites characterized by repeated failure, pioneers may dominate indefinitely (Orme, 1990;cf.…”
Section: Slopes Affected By Slope Failure and Mass Movementmentioning
confidence: 85%
“…These findings suggest that revegetated landslides may greatly affect the land scape-scale diversity of forested mountain environments. Most scholars tracking revegetation of scars over time have reported predictable successional changes in composition and structure (Johnson, 1976;Hupp, 1983;Mark et al, 1989). Because of inherent variation among different scars (Flaccus, 1959;Miles and Swanson, 1986;Guariguata, 1990), however, revegetation patterns revealed by chronosequences of landslide scars often are less detailed and predictable.…”
Section: Slopes Affected By Slope Failure and Mass Movementmentioning
confidence: 97%
See 1 more Smart Citation
“…Landslides are more infrequent than tree fall disturbances (Garwood 1979), but the scale is larger. After landslides, pioneer tree species may colonize immediately and remain for a century or more (Mark et al 1989). Brokaw (1987) showed that uncommon pioneer species, some of which are tall, long-lived species, may be vestiges of previous patterns of secondary succession.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently the time between disturbance and the establishment of the first tree in a cohort could vary considerably. Observations of vegetation colonisation on over twenty surfaces of known age since disturbance indicate that the first appearance of the species we include in this study takes from 3^0 years (Baxter & Norton 1989;Bray 1989;Mark et al 1989;A. Wells, unpubl.…”
Section: The Timing Of Disturbance Eventsmentioning
confidence: 99%